2017
DOI: 10.3945/jn.117.247775
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Selenotranscriptomes and Selenium Concentrations in Response to Dietary Selenium Deficiency and Age Reveal Common and Distinct Patterns by Tissue and Sex in Telomere-Dysfunctional Mice

Abstract: The hierarchies of tissue selenium distribution and selenotranscriptomes are thought to critically affect healthspan and longevity. We determined selenium status and selenotranscriptomes in response to long-term dietary selenium deficiency and age in tissues of male and female mice. Weanling telomerase RNA component knockout C57BL/6 mice were fed a selenium-deficient (0.03 mg Se/kg) Torula yeast-based AIN-93G diet or a diet supplemented with sodium selenate (0.15 mg Se/kg) until age 18 or 24 mo. Plasma, hearts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…As expected, a significantly lower whole-blood Se concentration was observed in Se-deficient mice compared to the Se-adequate and Se-supplemented groups at the study endpoint i.e., week 8. This finding is supported, to some extent, by a recent report [57] where it was shown that plasma Se concentration significantly declined in telomere-dysfunctional aged female mice (C57BL/6) fed a Se-deficient diet (Se-yeast 0.03 mg Se/kg) compared to those fed an adequate inorganic-Se diet (0.15 mg Se/kg) until aged 18 or 24 months; this decline was more pronounced in the latter age group. Similarly, in two very recent studies [42,43] on young female BALB/c mice, a significant reduction in whole-blood Se levels was reported following a three-month long feeding with a Se-deficient (0.02 mg Se/kg) diet.…”
Section: Blood Se Status and Total Antioxidant Capacitysupporting
confidence: 83%
See 3 more Smart Citations
“…As expected, a significantly lower whole-blood Se concentration was observed in Se-deficient mice compared to the Se-adequate and Se-supplemented groups at the study endpoint i.e., week 8. This finding is supported, to some extent, by a recent report [57] where it was shown that plasma Se concentration significantly declined in telomere-dysfunctional aged female mice (C57BL/6) fed a Se-deficient diet (Se-yeast 0.03 mg Se/kg) compared to those fed an adequate inorganic-Se diet (0.15 mg Se/kg) until aged 18 or 24 months; this decline was more pronounced in the latter age group. Similarly, in two very recent studies [42,43] on young female BALB/c mice, a significant reduction in whole-blood Se levels was reported following a three-month long feeding with a Se-deficient (0.02 mg Se/kg) diet.…”
Section: Blood Se Status and Total Antioxidant Capacitysupporting
confidence: 83%
“…Similarly, recently it was shown that Se deficiency downregulated several selenoproteins, including Gpx1, Gpx3, and Gpx4, in an organ-specific manner in mice [89]. Interestingly, long-term Se deficiency and age also significantly downregulated mRNA levels of many selenoproteins such as Gpx1, Gpx3, and Gpx4 in a tissue-specific manner in aged female G3 Terc −/− C57BL/6 mice [57]. In any case, precise fundamental basis of this tissue-specific hierarchical selenotranscriptomic regulation by dietary Se deficiency still remains poorly elucidated [57].…”
Section: Expression Of Gpx1 Gpx3 Gpx4 Selenof Bcl-2 and P21mentioning
confidence: 72%
See 2 more Smart Citations
“…In mice, selenium deficiency has been previously demonstrated to increase expression of GPx2 in the gastrointestinal tract [40]; however, this is the first study to investigate the effects of dietary selenium deficiency on foetal selenoprotein expression. Expression of DIO2 and SelenoN in kidneys has also been recognised to upregulate in response to dietary selenium deficiency [41], with age also playing a factor in upregulation of several others. Cao et.…”
Section: Fetal Selenoproteinsmentioning
confidence: 99%